Mechanisms of Cancer-Induced Bone Pain - Wang X; Li L; Wang Y (Journal of Pain Research)
Xuejuan Wang, Li Li, Yun Wang Department of Anesthesiology, Beijing Friendship Hospital, Capital Medical University, Beijing, People’s Republic of ChinaCorrespondence: Yun Wang, Department of anesthesiology, Beijing Friendship Hospital, Capital Medical University, No. 95, Yong’an Road, Xicheng District, Beijing, 100050, People’s Republic of China, Email wangyun129@ccmu.edu.cnAbstract: Bone is a common site of advanced cancer metastasis, second only to the lungs and liver. Cancer-induced bone pain (CIBP) is a persistent and intense pain that is caused by a combination of inflammatory and neuropathic factors. As CIBP progresses, the degree of pain intensifies. Despite advancements in medical technology, the treatment outcomes of patients with CIBP remain unsatisfactory, and severe pain can typically only be controlled with opioid medications. However, patients treated with opioid medications often develop tolerance. Therefore, they may require dose increases, which can increase the severity of opioid-induced side effects, in turn influencing quality of life. The peripheral mechanisms of CIBP primarily involve bone tissue damage, tumor microenvironment formation, and changes in the dorsal root ganglion. The central mechanisms usually involve biochemical and electrophysiological changes in the spinal cord and brain. The spinal cord is the main processing center for nociceptive signals. When tumor cells produce inflammatory mediators that acidify the microenvironment or damage nerve endings, the spinal cord becomes excessively stimulated, resulting in increased or prolonged pain signals that propagate to the higher central nervous system through the ascending pathway. There are substantial differences in the pain generation mechanisms between CIBP and common inflammatory and neuropathic pain. Therefore, understanding the mechanisms underpinning CIBP development at the level of the spinal cord is crucial for optimizing pain management. This study explores the pathogenesis of CIBP at the level of the spinal cord and describes recently proposed treatment methods for CIBP.Keywords: Cancer-induced bone pain, spinal cord, microglia, neuron, astrocyte